Role of epigenetics and the transcription factor Sp1 in the expression of the D prostanoid receptor 1 in human cartilage - Najar, Mehdi; Alsabri, Sami G.; Guedi, Gadid G.; Merimi, Makram; Lavoie, Frédéric; Grabs, Detlev; Pelletier, Jean-Pierre; Martel-Pelletier, Johanne; Benderdour, Mohamed; Fahmi, Hassan (Frontiers in Cell and Developmental Biology, 2023)
D prostanoid receptor 1 (DP1), a prostaglandin D2 receptor, plays a central role in the modulation of inflammation and cartilage metabolism. We have previously shown that activation of DP1 signaling downregulated catabolic responses in cultured chondrocytes and was protective in mouse osteoarthritis (OA). However, the mechanisms underlying its transcriptional regulation in cartilage remained poorly understood.In the present study, we aimed to characterize the human DP1 promoter and the role of DNA methylation in DP1 expression in chondrocytes. In addition, we analyzed the expression level and methylation status of the DP1 gene promoter in normal and OA cartilage.Deletion and site-directed mutagenesis analyses identified a minimal promoter region (-250/-120) containing three binding sites for specificity protein 1 (Sp1). Binding of Sp1 to the DP1 promoter was confirmed using electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assays. Treatment with the Sp1 inhibitor mithramycin A reduced DP1 promoter activity and DP1 mRNA expression. Inhibition of DNA methylation by 5-Aza-2'-deoxycytidine upregulated DP1 expression, and in vitro methylation reduced the DP1 promoter activity. Neither the methylation status of the DP1 promoter nor the DP1 expression level were different between normal and OA cartilage.In conclusion, our results suggest that the transcription factor Sp1 and DNA methylation are important determinants of DP1 transcription regulation. They also suggest that the methylation status and expression level of DP1 are not altered in OA cartilage. These findings will improve our understanding of the regulatory mechanisms of DP1 transcription and may facilitate the development of intervention strategies involving DP1.